Combined Training Programm For Cladding And Endurance And Its Conséquences On The Performance Of Algérian Walkers - Boufaroua, Mokhtar; Mimouni, Nabila (Journal of Sport Science Technology and Physical Activities, 2020)
The purpose of this study was to show the effect of simultaneous training (of core and endurance) on the performance of Algerian walkers. We compared two groups (control group (GC) and experimental group (GT)) composed of 12 practicing athletes race walking and members of the national team training under the guidelines of the same coach using only endurance training for the first group, while the second group undertook a simultaneous training of core training and 'endurance. The study lasted for a total of 08 weeks with a pre-test phase before training and a post-test phase after training. We were able to measure the VO2max, the VMA, the 05 km race walk, the core stability with the double leg lowering and the Mc Gills test. The results show that performance improved for both groups on the main endurance performance variables VO2max, VMA and 05 km race walk), while the experimental group showed no significant improvement Compared to the control group after the various training sessions.We can conclude that simultaneous training of core and endurance has no more influence on endurance performance than training based completely on endurance.